STUDY AND ANALYSIS OF AN IMAGE BY AN OPTICAL-ELECTRONIC SYSTEM - Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Some interrelations of two-dimensional image of optic electronic devices are developed in this paper. The informativity of the object image is investigated through the use of multi spectral optic system, limited by aberrations.